Enhanced electrooxidation of per and polyfluoroalkyl substances on Boron doped diamond anode in the presence of vacuum ultraviolet irradiation - Yaye Wang; Haibo Xu; Ruoyang Li (Scientific Reports)
Abstract Degradation of per- and polyfluoroalkyl substances (PFASs) via photochemical and electrochemical methods is of great interest in persistent organic pollutants treatment. This study systematically evaluated the degradation of two representative PFASs, perfluorooctanoic acid (PFOA) and perfluorohexanoic acid (PFHxA), on boron-doped diamond (BDD) anode combined with vacuum ultraviolet (VUV) irradiation. Although VUV irradiation did not show effectiveness on PFOA and PFHxA removal, it greatly enhanced the degradation efficiency of PFOA and PFHxA in electrooxidation (EO) system. Surface area normalized pseudo-first order rate constants of PFOA and PFHxA increased 37.2% and 70.1% in the presence of VUV irradiation at 10 mA∙cm−2, respectively. The experiment results along with Time-Dependent Density Functional Theory (TDDFT) computation reveal that excited states of PFOA and PFHxA induced by absorbing VUV irradiation reduced the energy difference (ΔE) required to lose an electron, and thus accelerated the direct electron transfer process. PFASs degradation were also promoted in the real industrial wastewater in electrooxidation system in combination of VUV irradiation.